BRITISH WOMEN IN MOVIE PRIDE AND PREJUDICE DIRECTED BY JOE WRIGHT: A FEMINIST LITERARY STUDY - Kholifatur Rosyida; Indra Tjahyadi (JURNAL LITERASI, 2022)
This research focuses on British women who are represented in the film Pride and Prejudice directed by Joe Wright. This study uses a feminist literary approach. The qualitative-descriptive method is used as the basis of the research method. Based on the analysis conducted, it was found that the Representation of the British women in Pride and Prejudice movie is differences between British women and Elizabeth Bennet. Especially for characters, in British women intelligent cause education but in Elizabeth be brilliant because she loves to read very much and get knowledge from many sources.